Embolic Stroke of Undetermined Source: Approaches in Risk Stratification for Cardioembolism. Issue 12 (28th October 2021) - Bhat, Aditya; Mahajan, Vipul; Chen, Henry H.L.; Gan, Gary C.H.; Pontes-Neto, Octavio M.; Tan, Timothy C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Ischemic stroke is a leading cause of morbidity and mortality worldwide. Embolic stroke of undetermined source has been recently proposed to categorize nonlacunar ischemic strokes without confirmed etiology after adequate investigation with a likely embolic stroke mechanism. A strategy of empirical anticoagulation for embolic stroke of undetermined source patients is attractive but may only be beneficial in a select subset of patients. Strategies which would help identify the subset of embolic stroke of undetermined source patients most likely to have cardioembolic origin of stroke, and hence benefit from anticoagulation, are needed. This article will review current evidence which may be useful in the development of a risk stratification approach based on arrhythmia monitoring, cardiac imaging, and clinical risk stratification. This approach may be beneficial in clinical practice in improving patient outcomes and reducing stroke recurrence in this population; however, further work is required with active trials underway.